Biosorption of iron (II) and methylene blue using tea waste - Nur Izdiharr, Zainol (2010)
The used of tea waste as a low-cost natural biosorbent for the removal of heavy metals and dyes had been investigated. The high concentration of Iron (II) and methylene blue caused environment problem. The purpose of this study is to investigate the capability of tea waste as the biosorbent in removal of Iron (II) and methylene blue from aqueous solution in laboratory scale. Batch experiments were conducted to determine the effects of varying biosorbent dosage, pH and contact time of adsorption.. Tea waste was prepared by dried with 60⁰C for 24 hours, blended and sieved into 400µm. This experiment was carried out in conical flasks within initial concentration for methylene blue is 10mg/L and Iron (II) solution is 500mg/L. Then agitated in orbital shaker CERTOMAT S-II with oscillation 200rpm. For methylene blue, UV-Vis Spectrophotometer had been used to measure the absorbance while HACH Spectrophotometer DR/2400 was used to measure the final concentration of the Iron solution. The biosorption was found to be maximum dosage is 1.0g for both solution. For parameter contact time, the biosorption started to be constant at 330 minutes for iron solution and 180 minutes for methylene blue. By varying pH range of 1 – 12, the optimum removal of Iron (II) achieved at pH 6 and methylene blue at pH 8. As the conclusion, tea waste can remove 95% - 99% Iron(II) and 85% - 99% Methylene Blue. Tea waste can be very suitable for development as an efficient biosorbent in removing Iron(II) and methylene blue for wastewater treatment.